Pendidikan Seni, Hubungannya dengan Ambang Sadar, Imajinasi dan Kreativitas serta Manfaatnya untuk Proses Belajar yang Bermutu - Primadi Tabrani (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2015)
It seems obvious that all theories of learning, teaching, training, and curriculum are borrowed from developed countries. However, from past and present experience, all of those theories will be less suitable for Indonesia. Therefore, we need the courage to study what happened in the West and compare the results with our own traditional education. Based on our own researches, then we can generate what is the present-day modern education of Indonesia.This article discusses about